Afroestricus, a new Afrotropical Ommatine (Diptera: Asilidae) genus with twenty species and two species groups - Scarbrough, Aubrey G. (Zootaxa, 2005)
The new genus Afroestricus (Diptera: Asilidae) with 20 species, is described. Included are: A. abyssinia sp. n.; A. chiastoneurus (Speiser), A. eminentis, sp. n.; A. fulaui, sp. n.; A. hamulus, sp. n.; A. insectaris, sp. n.; A. kimerus, sp. n.; A. macroscelis (Bezzi), A. minutus (Bromley), A. morani, sp. n.; A. persuasus (Oldroyd), A. sadaukii, sp. n.; A. sankofa, sp. n.; A. variabilis (Engel), A. varipes (Curran), A. velatus, sp. n.; A. verutus, sp. n.; A. victus, sp. n.; A. vittatus (Curran), and A. vorax, sp. n. Afroestricus is distinctive in the following combination of characters: moderately gibbose face; frons with a wide, lateral, stripe of numerous setae; fore femur with a stout preapical, anteroventral bristle; and a prominent epiphallus that conceals the distiphallus dorsally, characters that are not congruent with Ommatius. New combinations include: A. chiastoneurus, A. macroscelis, A. minutus, A. persuasus, A. variabilis, A. varipes, and A. vittatus. New synonymies include: senax Bromley = chiastroneurus Speiser; munroi Bromley and bevisi Bromley = variabilis Engel; and garambensis Oldroyd = varipes Curran. The species are assigned to the macroscelis and minutus species groups based largely upon wing venation. The genus is largely confined to the Afrotropical region, between 17°N and 31°S latitude, with only the range of A. vittatus extending into western Yemen. The species show a relatively high level of sympatry. Descriptions, illustrations, and a key to the species are included. A brief discussion of the distribution and phenology of the species and a provisional key to the current Afrotropical genera and subgenera of Ommatiinae are also provided.